The Role of Village Libraries in Supporting the Women-Friendly and Child-Caring Village Program - Tri Soesantari; Fitri Mutia; Endang Gunarti (Universitas Lambung Mangkurat, 2024)
This community partnership program focuses on groups often experiencing discrimination, namely women, children, and vulnerable communities (including those with disabilities). This PKM (Community Partnership Program) aims to create a library environment that is friendly to women and attentive to children, thereby supporting the SDGs (Sustainable Development Goals) or sustainable village programs. It aims to increase village community awareness about gender equality and child protection issues through the library. Additionally, it seeks to enhance the knowledge and skills of library staff regarding gender equality and child protection issues. The program also involves increasing the number of books that support gender equality, women's rights, and child protection in the village library. This community partnership program implements the PAR (Participatory Action Research) method, aiming to increase active community involvement, sustainability, and positive impacts of the village library program in supporting the Women-Friendly and Child-Caring Village Program. The activities were conducted in Bicak Village, Trowulan Subdistrict, Mojokerto Regency. The results of this community partnership program include a 100% increase in community understanding of the role of the Village Library in supporting the SDGs and the Women-Friendly, Child-Caring, and Social Inclusion Village Program. After the socialisation activities, 95.7% of the community became more interested in utilising the collections and services available at the Bicak Village Library. The technical guidance activities for managers improved library management development and enhanced the knowledge and understanding of library managers regarding the library's role in gender equality and child protection. This PKM activity demonstrated that 100% of respondents believe the village library can support the Women-Friendly, Child-Caring, and Social Inclusion Village Program. This establishes Bicak Village as a friendly village for women, children, and vulnerable communities and achieves sustainable village development through the role of the village library.